2014
DOI: 10.1002/hep.27014
|View full text |Cite
|
Sign up to set email alerts
|

Opposite association between diabetes, dyslipidemia, and hepatocellular carcinoma mortality in the middle-aged and elderly

Abstract: Limited data exist regarding metabolic risk factors for deaths from hepatocellular carcinoma (HCC) in aging individuals. We investigated the association between diabetes, dyslipidemia, and HCC mortality in those aged 40 years or more (middle-aged and elderly). In this prospective cohort study based on nationwide health screening units, we consecutively followed middle-aged and elderly participants who had no chronic hepatitis B or C virus infection and received health screening from January 1 1998 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
5
45
0
2
Order By: Relevance
“…Few studies have examined the association between WC and risk of liver cancer (1214) and the results are mixed. A large European cohort study identified 177 liver cancers and reported HRs for the associations of WC (per 5 cm) and liver cancer risk that were similar with (HR: 1.29) and without (HR: 1.25) control for BMI (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have examined the association between WC and risk of liver cancer (1214) and the results are mixed. A large European cohort study identified 177 liver cancers and reported HRs for the associations of WC (per 5 cm) and liver cancer risk that were similar with (HR: 1.29) and without (HR: 1.25) control for BMI (14).…”
Section: Discussionmentioning
confidence: 99%
“…To date, U.S.-based prospective studies on this topic are especially rare: a two-fold higher risk of HCC was reported when comparing obese (≥30 kg/m 2 ) to normal BMI (18.5<25 kg/m 2 ) in a cohort study of 2,126 cirrhosis patients (11). The few prospective studies that examined the association between waist circumference (WC), an indicator of central adiposity, and liver cancer risk are somewhat conflicting, likely due to small sample sizes, but generally suggest higher risk with increasing WC (1214). These observations are supported by findings that general and central adiposity are associated with higher risks of nonalcoholic fatty liver disease (NAFLD) and the more severe nonalcoholic steatohepatitis (NASH), both of which are major risk factors for liver cancer (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in concert with the recent epidemic of obesity and metabolic syndrome in developed countries, the incidence and prevalence of non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH) have also increased, and today they represent rapidly growing causes of end‐stage liver disease and HCC . Moreover, regardless of the aetiology of liver disease, metabolic disorders, such as obesity and diabetes, contribute to hepato‐cancerogenesis . Indeed, there are well established pathophysiological mechanisms linking obesity, diabetes and HCC .…”
Section: Introductionmentioning
confidence: 99%
“…The International Diabetes Federation proposed that the causes for increased diabetes prevalence are population ageing and unhealthy lifestyle behaviors, including physical inactivity, smoking, alcohol consumption and an unhealthy diet. Recent epidemiological findings of cohort and case‐control studies have indicated a link between Type 2 diabetes and cancer in several organs, particularly the liver . Type 2 diabetes mellitus and many types of cancer share common risk factors such as smoking, alcohol consumption, obesity, physical inactivity, a high calorie intake and particularly saturated fat intake .…”
mentioning
confidence: 99%